Role of nuclear protein Akirin in the modulation of female reproduction in Nilaparvata lugens (Hemiptera: Delphacidae) - Gou, Feiyan; Zhang, Daowei; Chen, Siqi; Zhang, Mingjing; Chen, Jing (Frontiers in Physiology, 2024)
Akirin as a highly conserved transcription factor, exerts a profound influence on the growth, development, immune response, and reproductive processes in animals. The brown planthopper (BPH), Nilaparvata lugens, a major pest in rice production in Asia, possesses high reproductive capacity, a critical factor contributing to reduced rice yields. Here, using BPH genome data, we screened for an Akirin gene (NlAkirin). An analysis of tissue-specific expressions showed that NlAkirin was expressed in all tissues tested in female BPH, but its expression level was highest in the ovary. After inhibiting the mRNA expression of NlAkirin in BPH females, the number of eggs laid, hatching rate, and number of ovarioles decreased. Transcriptome sequencing was performed, following a NlAkirin double-stranded RNA treatment. Compared with the genes of the control, which was injected with GFP double-stranded RNA, there were 438 upregulated genes and 1012 downregulated genes; the expression of vitellogenin (Vg) and vitellogenin receptor (VgR) genes as well as the mRNA expression of genes related to the target of rapamycin (TOR), juvenile hormone (JH), and insulin pathways involved in Vg synthesis was significantly downregulated. As a result of NlAkirin knockdown, the titers of JH III and Ecdysone (Ecd) were downregulated in unmated females but returned to normal levels in mated females. The ovarian protein contents in both unmated and mated females were downregulated. In summary, our results indicate that NlAkirin modulates the reproduction of female BPH by inhibiting gene expression in the Vg network.